2010
DOI: 10.1136/tc.2009.030460
|View full text |Cite
|
Sign up to set email alerts
|

Indoor secondhand tobacco smoke emission levels in six Lebanese cities

Abstract: BackgroundTo date, Lebanon has failed to enact comprehensive clean indoor air laws despite ratification of the Framework Convention on Tobacco Control (FCTC), which calls for the protection of non-smokers from exposure to secondhand tobacco smoke (SHS). Complicating the problem of SHS exposure in Lebanon is the widespread use of the tobacco water-pipe. While most research on SHS has involved cigarette smoking as a source of emissions, other sources, including tobacco water-pipes, may be an important contributo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
2
23
0
Order By: Relevance
“…Moreover, Hammal et al 34 observed mean indoor PM 2.5 levels of 264 μg/m 3 arising from the use of tobacco-free ‘herbal’ WP products. The particulate matter levels detected among WP cafes in Qatar also compare closely with those observed in non-smoke-free public venues (predominantly containing cigarettes) reported elsewhere in the EMR, and throughout the world 21 28 35 36…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, Hammal et al 34 observed mean indoor PM 2.5 levels of 264 μg/m 3 arising from the use of tobacco-free ‘herbal’ WP products. The particulate matter levels detected among WP cafes in Qatar also compare closely with those observed in non-smoke-free public venues (predominantly containing cigarettes) reported elsewhere in the EMR, and throughout the world 21 28 35 36…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, these results may not be representative of all public venues in Gaza city. However, the levels measured are consistent with monitoring conducting in many other jurisdictions around the world which have not banned indoor smoking [13][14][15]. Finally, smoking may not have been the only source of indoor particulate pollution.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, these data are consistent with measurements taken from indoor public venues in other EMR countries. For example, high PM 2.5 levels have been found in indoor public venues with observed smoking in Syria (372 µg/m 3 ), Tunisia (328 µg/m 3 ) and Lebanon (342 µg/m 3 ) [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations could be supplemented by the monitoring of air quality in indoor places that provides a more accurate indicator of compliance with the smoke free legislation. This is particularly useful as we have data from 2008 on air quality prior to the implementation of the tobacco control law that could be used for comparison 28 . In the 2009-2011 strategic plan, the National Tobacco Control Program has stated that such monitoring would indeed take place in indoor public places in 40 key areas to monitor compliance.…”
Section: Resultsmentioning
confidence: 99%